In Vitro and In Vivo Activities of Novel 2-(Thiazol-2-ylthio)-1β-Methylcarbapenems with Potent Activities against Multiresistant Gram-Positive Bacteria - Ueda, Yutaka (American Society for Microbiology, 2003)
SM-197436, SM-232721, and SM-232724 are new 1β-methylcarbapenems with a unique 4-substituted thiazol-2-ylthio moiety at the C-2 side chain. In agar dilution susceptibility testing these novel carbapenems were active against methicillin-resistant Staphylococcus aureus (MRSA) and Staphylococcus epidermidis (MRSE) with a MIC(90) of ≤4 μg/ml. Furthermore, SM-232724 showed strong bactericidal activity against MRSA, in contrast to linezolid, which was bacteriostatic up to four times the MIC. SM-232724 showed good therapeutic efficacy comparable to those of vancomycin and linezolid against systemic infections of MRSA in cyclophosphamide-treated mice. The MICs of SM-197436, SM-232721, and SM-232724 for streptococci, including penicillin-intermediate and penicillin-resistant Streptococcus pneumoniae strains, ranged from ≤0.063 to 0.5 μg/ml. These drugs were the most active β-lactams tested against Enterococcus faecium, and the MIC(90) s for ampicillin-resistant E. faecium ranged between 8 and 16 μg/ml, which were slightly higher than the value for linezolid. However, time-kill assays revealed the superior bactericidal activity of SM-232724 compared to those of quinupristin-dalfopristin and linezolid against an E. faecium strain with a 4-log reduction in CFU at four times the MIC after 24 h of exposure to antibiotics. In addition, SM-232724 significantly reduced the numbers of bacteria in a murine abscess model with the E. faecium strain: its efficacy was superior to that of linezolid, although the MICs (2 μg/ml) of these two agents are the same. Among gram-negative bacteria, these three carbapenems were highly active against Haemophilus influenzae (including ampicillin-resistant strains), Moraxella catarrhalis, and Bacteroides fragilis, and showed antibacterial activity equivalent to that of imipenem for Escherichia coli, Klebsiella pneumoniae, and Proteus spp. Thus, these new carbapenems are promising candidates for agents to treat nosocomial bacterial infections by gram-positive and gram-negative bacteria, especially multiresistant gram-positive cocci, including MRSA and vancomycin-resistant enterococci.